2017 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2017
DOI: 10.1109/iros.2017.8206210
|View full text |Cite
|
Sign up to set email alerts
|

Semi-autonomous electrosurgery for tumor resection using a multi-degree of freedom electrosurgical tool and visual servoing

Abstract: This paper specifies a surgical robot performing semi-autonomous electrosurgery for tumor resection and evaluates its accuracy using a visual servoing paradigm. We describe the design and integration of a novel, multi-degree of freedom electrosurgical tool for the smart tissue autonomous robot (STAR). Standardized line tests are executed to determine ideal cut parameters in three different types of porcine tissue. STAR is then programmed with the ideal cut setting for porcine tissue and compared against expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…There are several other systems aimed at autonomous surgeries (or part thereof) in different areas (orthopaedic, radiotherapy, etc.). There also exist several robots, not designed for autonomy, which are adapted for autonomous tasks (Raven, DVRK) …”
Section: Common Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…There are several other systems aimed at autonomous surgeries (or part thereof) in different areas (orthopaedic, radiotherapy, etc.). There also exist several robots, not designed for autonomy, which are adapted for autonomous tasks (Raven, DVRK) …”
Section: Common Criteriamentioning
confidence: 99%
“…There also exist several robots, not designed for autonomy, which are adapted for autonomous tasks (Raven, DVRK). 16…”
Section: Common Criteriamentioning
confidence: 99%
“…Due to the combination of the coarser temporal and the finer spatiotemporal control in the overall control configuration, the results presented have a broad appeal in other applications involving complex multiscale spatiotemporal dynamics, such as, for example, robotic electrosurgery [41]. In this application, the motion of the cutting probe is strongly coupled to the spatiotemporal electrosurgical impact of the latter on the target tissues, and the near-field probe-tissue interaction process is best described by a complex time-fractional PDE [42].…”
Section: Discussionmentioning
confidence: 99%
“…used the same system in a porcine model to resect squamous cell carcinoma pseudo-tumors marked with NIRF fiducials. The authors found that although resection by STAR took longer, it was able to achieve more consistently with the targeted resection than a human surgeon 42 . Completely autonomous robotic surgeons with artificial intelligence are still in the realm of science fiction.…”
Section: Other Robot Technology On the Horizonmentioning
confidence: 99%